2023
DOI: 10.24276/rrecien2023.13.41.3-12
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico da síndrome respiratória aguda grave por COVID-19 em idosos

Abstract: A Coronavirus Disease (COVID-19) pode causar infecções respiratórias graves, cujas taxas de morbimortalidade são maiores em populações de risco, como os idosos, portadores de doenças crônicas e imunossuprimidos. Nesse sentido, este estudo descreve o perfil das internações por Síndrome Respiratória Aguda Grave (SRAG) relacionada à COVID-19 entre idosos, no Brasil, em 2020. Trata-se de um estudo epidemiológico descritivo com base nos registros disponibilizados pelo Departamento de informática do SUS. Os resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
4
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 3 publications
7
4
0
7
Order By: Relevance
“…Regarding skin color, data similar to the current research was identified in a Brazilian investigation among elderly people diagnosed with COVID-19 25 . However, a higher percentage of elderly people who self-declare black skin color was found in a national survey in Brazilian states, diverging from the present investigation .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding skin color, data similar to the current research was identified in a Brazilian investigation among elderly people diagnosed with COVID-19 25 . However, a higher percentage of elderly people who self-declare black skin color was found in a national survey in Brazilian states, diverging from the present investigation .…”
Section: Discussionsupporting
confidence: 87%
“…One of the factors that may justify this finding is that urban areas have a larger population of people, consisting of commercial areas, hospitals and companies, which generates greater movement and circulation of individuals, and therefore, the COVID-19 virus 27 . It is noteworthy that the high levels of existing pollution can increase the Considering the risk factors related to the outcome of death, a similar result was identified in a cross-sectional study in five regions of Brazil 25 . A systematic review found that morbidities such as diabetes mellitus, cardiovascular diseases, chronic obstructive pulmonary disease, high blood pressure and acute kidney injury represented an increased risk of mortality from COVID-19 29 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A presença de alterações em exames laboratoriais 11,14,17 e de imagem [11][12][13][14][15] , além de desfechos adversos, como a demanda por suporte ventilatório [10][11][12][13] e óbito 11,14 , também são características identificadas em uma parcela das pessoas idosas internadas com a doença.…”
Section: Introductionunclassified
“…Apesar da existência de pesquisas que identificaram as características das internações por covid-19 em pessoas idosas [10][11][12][13][14][15] , o conhecimento ainda precisa ser ampliado em Minas Gerais, um dos estados com maiores índice de envelhecimento 19 e registros de casos da doença 20 .…”
Section: Introductionunclassified